IMPLEMENTASI KEBIJAKAN PELESTARIAN BANGUNAN CAGAR BUDAYA KOTA LAMA SEMARANG - Alfirdania Saphira Dewi; Endang Larasati Setianingsih; Tri Yuniningsih (Journal of Public Policy and Management Review, 2023)
The policy for preserving cultural heritage buildings in the Old City of Semarang is the background for this research. Problems that arise: How is the implementation of the policy or preserving cultural heritage buildings in the Old City of Semarang? What are the policy actors for preserving cultural heritage buildings in the Old City of Semarang? The aim of the research is to analyze the content of the policy for preserving cultural heritage buildings in the Old City of Semarang and to analyze the policy factors for the revitalization of the Old City of Semarang. Efforts to answer the problems and objectives of the research were carried out using Donald Van Meter and Van Horn's theory of public policy implementation to see whether or not the implementation of the policy for preserving cultural heritage buildings in the Old City of Semarang was effective. To see the factors that influence policy, researchers used George Edward's theory which consists of 4 variables What was observed were communication, resources, disposition and bureaucratic structure. This research used descriptive qualitative methods. The object of the research is the policy for preserving cultural heritage buildings in the Semarang Old City area. The results of the research show that the Semarang City Regional Government has implemented the contents of Regional Regulation No. 2 of 2020 concerning the Preservation of Semarang Old City cultural heritage buildings in which the Semarang City Government and the stakeholders involved have implemented the Protection, Development and Utilization of the Old City Area well. Apart from that, the actors involved in this policy are members of BPK2L, the Culture and Tourism Service, PUPR Director General of Human Settlements, the Transportation Service, the Civil Service Police Unit, and the Spatial Planning Service. Supporting factors for implementing the policy for preserving cultural heritage buildings in the Old City of Semarang include good communication with the community and between stakeholders. Based on its resources, there are still many individual buildings that are difficult to preserve. It is hoped that the Semarang City Government can review the lists of cultural heritage buildings in the Old City of Semarang so that they can be arranged neatly, cleanly and orderly. So that it is not only cultural heritage buildings that are of interest to many tourists